The Fusion of Tradition and Modernity: Reviewing the Lyrics and Vocal Style of Chinese Art Songs - Lin, Li Mao; Sabri , Shafizan bin (Universitas Negeri Medan, 2025)
This study explores the characteristics of Chinese art songs, with a particular focus on their lyrics and vocal style, through a literature review approach. Chinese art songs (yishu gequ) emerged during the May Fourth Movement as a fusion of Western compositional techniques and traditional Chinese cultural elements. The lyrics are deeply rooted in Chinese ancient poetry, drawing on classical themes such as nature, emotions, and philosophy, while maintaining structural integrity through poetic forms like shi (詩) and ci (詞). The linguistic complexities of Mandarin Chinese, a tonal language, present unique challenges for composers in balancing melodic expression with tonal accuracy. Additionally, the vocal style integrates Western operatic traditions with elements from traditional Chinese vocal aesthetics, such as those found in Peking opera and folk music. Performers face interpretative challenges due to the hybrid nature of the genre, requiring technical mastery and cultural sensitivity. The findings highlight the cultural and artistic significance of Chinese art songs as a unique genre that bridges traditional Chinese heritage and modernity. This research underscores the importance of further study on the lyrics and vocal styles to enrich understanding and appreciation of this musical form.